2013
DOI: 10.1016/j.jval.2013.03.1149
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Comparison Of Discrete Choice Experiment And Best-Worst Scaling To Estimate Stakeholders' Risk Tolerance For Hip Replacement Surgery

Abstract: Background: Previous studies have been inconclusive regarding the validity and reliability of preference elicitation methods. Objective: The aim of this study was to compare the metrics obtained from a discrete choice experiment (DCE) and profile-case best-worst scaling (BWS) with respect to hip replacement. Methods: We surveyed the general US population of men aged 45 to 65 years, and potentially eligible for hip replacement surgery. The survey included sociodemographic questions, eight DCE questions, and twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…to make trade-offs among attributes). According to van Dijk et al (2013), the BWS tasks were perceived as being more difficult and took longer to complete than DCE tasks (van Dijk et al, 2013). This mixed evidence suggests that the 'validity and acceptability of the BWS method is not definite and requires further research'.…”
Section: Introductionmentioning
confidence: 99%
“…to make trade-offs among attributes). According to van Dijk et al (2013), the BWS tasks were perceived as being more difficult and took longer to complete than DCE tasks (van Dijk et al, 2013). This mixed evidence suggests that the 'validity and acceptability of the BWS method is not definite and requires further research'.…”
Section: Introductionmentioning
confidence: 99%
“…Tables 1, 2 and 3 show the characteristics of the eligible studies, while Tables 4, 5 and 6 show how understanding was defined, measured, and used within each eligible study. The majority of studies were DCEs (or studies about DCEs), with two BWS3 studies [38,39] and three studies including both a DCE and a BWS3 design [40][41][42]. Most were conducted in Europe (n = 24) and the UK (n = 17), followed by the US (n = 15) and Australia (n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in the literature have considered preference method appropriateness based on patients' preference for the elicitation task 11 and its difficulty. [8][9][10] Such studies are valuable but provide little practical guidance for a researcher who is planning a preference study. On the one hand, as this paper has shown, these factors are but a small share of the aspects the researcher should consider when choosing the preference elicitation method.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 The only aspects of method appropriateness considered in these studies were which methods the patients preferred 11 or found more difficult. [8][9][10] This paper reports a qualitative comparison of 2 methods, DCE and multicriteria decision analysis (MCDA) swing weighting (SW).…”
Section: Introductionmentioning
confidence: 99%